Diversity of pseudo-toothed birds (Pelagornithidae) from the Eocene of Antarctica. (21st March 2016) - Cenizo, Marcos; Hospitaleche, Carolina Acosta; Reguero, Marcelo
Abstract: The Antarctic pelagornithid record is restricted to few isolated remains from the Eocene of Seymour Island in the Antarctic Peninsula. Here we report the oldest Antarctic pseudo-toothed bird. It is represented by an incomplete humerus lacking its proximal end, which comes from the lower Eocene levels of the La Meseta Formation (Seymour Island). This new specimen facilitates a review of all known pelagornithids from this continent. Antarctic pelagornithids were classified into two morphotypes that exhibit a mix of putative plesiomorphic and derived characters. Considering the worldwide pelagornithid record and according to estimated wingspans, four approximate size-types were identified. The oldest Antarctic specimens (two fragmentary humeri, middle Ypresian) were assigned to morphotype 1 and correspond to the large size-type. The younger materials (Bartonian/?Priabonian) here assigned to morphotype 2 (some cranial remains, fragmentary tarsometatarsus and humerus) correspond to the giant size-type and represent one of the largest known pseudo-toothed birds. Even though species level phylogenetic affinities of Pelagornithidae remain poorly resolved, three key evolutionary events can be recognized: (1) the disappearance of Dasornis in the Early Eocene and the appearance of more advanced forms with a trend to the specialization of large soaring capacity, (2) the origin of Pelagornis sensu lato species in the early Oligocene, and (3) the appearance and dominance of a highly specialized terminal group at Mio/Pliocene time span.